Game theory based autonomous DSM algorithm design - Lee, Zheng Yi (Nanyang Technological University, 2020)
With how fast the world is evolving nowadays, there is an ever-continuous increasing need for energy and a higher demand for energy. This increase in demand creates challenges for utilities as thy would have to match this increase in demand and generate sufficient amount of electricity. Hence, it is important to use Demand Side Management (DSM) to help to utilise our current energy in a more efficient manner